2018
DOI: 10.20945/2359-3997000000074
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid cancer burden and economic impact on the Brazilian public health system

Abstract: Objective: Recent data indicates an increasing incidence of thyroid cancer not accompanied by a proportional increase in mortality, suggesting overdiagnosis, which may represent a big public health problem, particularly where resources are scarce. This article aims to describe and evaluate the procedures related to investigation of thyroid nodules and treatment and follow-up of thyroid cancer and the costs for the Brazilian public health system between 2008 and 2015. Materials and methods: Data on procedures r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 44 publications
(50 reference statements)
2
18
0
3
Order By: Relevance
“…We observed that the majority of thyroid cancer cases were of low risk of recurrence and mortality. Moreover, we found that more than half of thyroid cancers were diagnosed incidentally, and the minority of patients presented with symptoms resembling findings in countries where thyroid cancer overdiagnosis drives increasing incident trends [34][35][36][37] .…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…We observed that the majority of thyroid cancer cases were of low risk of recurrence and mortality. Moreover, we found that more than half of thyroid cancers were diagnosed incidentally, and the minority of patients presented with symptoms resembling findings in countries where thyroid cancer overdiagnosis drives increasing incident trends [34][35][36][37] .…”
Section: Discussionsupporting
confidence: 63%
“…The very low and low risk of recurrence was 18.1% (79) and 62% (271) respectively. An analysis of 319 patients with nonmetastatic thyroid cancer showed that 10.7% (34) of patients had surgical complications. Moreover, around 62.5% (80 from 128 patients with thyroglobulin laboratory results) of TC patients had a stimulated-thyroglobulin (sTg) value equal or higher than 2 ng/ml.…”
Section: Introductionmentioning
confidence: 99%
“…T hyroid cancer is the most common malignancy of the endocrine system, and its global incidence has increased in recent years; 52 070 new cases are expected to occur in the United States in 2019 (1,2). The majority of thyroid cancers originate from the follicular cells; in terms of histological and clinical behavior, these cancers are classified as well-differentiated, poorly differentiated and undifferentiated (3).…”
mentioning
confidence: 99%
“…We observed that the majority of thyroid cancer cases were of low risk of recurrence and mortality. Moreover, we found that more than half of thyroid cancers were diagnosed incidentally, and the minority of patients presented with symptoms resembling ndings in countries where thyroid cancer overdiagnosis drives increasing incident trends [32][33][34][35] . The driver of incidental thyroid cancer in this cohort was the used of neck ultrasound.…”
Section: Discussionmentioning
confidence: 75%